Respostas
respondido por:
1
é só vc calcular utilizando o produto notável.
x²+2.x.2+2²=x²+2.x.1+1²+x²
x²+4x+4=x²+2x+1+x²
x²+4x+4-x²-2x-1-x²=0
-x²+2x+3=0 (-1)
x²-2x-3=0
Δ= (-2)²-4.1.(-3)
Δ=4+12
Δ=16
2+4/2 x'= 6/2=3
2-4/2 x"= -2/2=-1
x²+2.x.2+2²=x²+2.x.1+1²+x²
x²+4x+4=x²+2x+1+x²
x²+4x+4-x²-2x-1-x²=0
-x²+2x+3=0 (-1)
x²-2x-3=0
Δ= (-2)²-4.1.(-3)
Δ=4+12
Δ=16
2+4/2 x'= 6/2=3
2-4/2 x"= -2/2=-1
larissalelis:
obrigada vc acaba de me salvar
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás